Augusta J. Evans letter - Evans, Augusta J. (Augusta Jane), 1835-1909.
ALS (Mobile, Ala.; 1895 October 24) from Evans to her friend Lettie Clark concerning a diphtheria outbreak and family matters.
Author. Married L.M. Wilson, 1868. Also known as Augusta Evans Wilson.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clark, Lettie -- Correspondence; Diphtheria -- Alabama -- Mobile; Mobile (Ala.) -- Social life and customs; Authors